Implementasi NAS Untuk Penyimpanan Lokal di Biro Kominfo Pesantren Tahfizh Daarul Qur’an - Affandi, Firman; Mu’afa, Naufal; Satriya, Irfan; Fajri, Annur; Muclis (LPPM STMIK ANTAR BANGSA, 2025)
The rapid development of digital data in educational institutions demands efficient management solutions. The Information Bureau at Pesantren Tahfizh Daarul Quran faced issues like data duplication, limited access, and hardware failures causing data loss. To resolve these, a Network Attached Storage (NAS) system was implemented to centralize storage, improve accessibility, and enhance security. This study assesses the impact of NAS by comparing pre- and post-implementation conditions, showing improvements in operational efficiency and data management, and providing insights for similar institutions seeking technological solutions.